Factors Influencing Farmers’ Knowledge, Capacity, and Practice of Conservation Agriculture in Bangladesh - Riffat Ara Zannat Tama; Liu Ying; Md Mahmudul Hoque (European Scientific Journal, ESJ, 2025)
Conservation Agriculture (CA) is an alternative to the conventional farming system, which is considered a way of achieving climate-smart agriculture. Despite various CA support programs and promotional activities in Bangladesh, a major portion of CA farmers are reluctant to continue CA farming. This research aimed to reveal the extent and difficulties of continuing the practice and the gap between farmers’ knowledge, ability, and performance. To collect data, we conducted a cross-sectional survey of 201 CA-adopting farmers from northern districts, namely Rajshahi, Rangpur, and Dinajpur. Results show that, among all components of CA practices in the area, most of the farmers regularly practice minimum tillage. The results also indicate that average income, access to and availability of machinery, and the knowledge gap are all commonly significant and have a big effect on the three dependent variables: the can-do gap, the know-can gap, and the know gap. The evidence indicates that reducing these gaps requires subsidies for resource-poor farmers and easy access to the machinery needed for CA practice. Public or private investments, or a combination of both, can effectively reduce these gaps.